Outcomes of minimal access retroperitoneal para-aortic lymphadenectomy in patients with locally advanced cervical cancer - Claire Newton; Radha Graham; Viola Liberale; Matthew Burnell; Usha Menon; Tim Mould; Adeola Olaitan; Nicola Macdonald; Martin Widschwendter; Kostas Doufekas; Mary McCormack; Anita Mitra; et al. (Taylor & Francis Group, 2024)
Background To evaluate outcomes of laparoscopic retroperitoneal para-aortic lymphadenectomy for stage 1b3-3b cervical cancer.Methods Pathology databases searched for all para-aortic lymphadenectomy cases 2005-2016. Descriptive statistics were used to analyse baseline characteristics, cox models for treatment affect after accounting for variables, and Kaplan Meier curves for survival (STATA v15).Results 191 patients had 1b3-3b cervical cancer of which 110 patients had Para-aortic lymphadenectomy. 8 (7.3%) patients stage 1b3, 82 (74.6%) stage 2b, and 20 (18.1%) stage 3b cervical cancer. Mean lymph node count 11.7 (SD7.6). The intra-operative and post-operative 30 day complication rates were 8.8% (CI: 4.3%, 15.7%) and 5.3% (CI: 1.9%, 11.2%) respectively.Para-aortic nodes were apparently positive on CT/MRI in 5/110 (5%) cases. Cancer was found in 10 (8.9%, CI: 4.3%, 15.7%) cases on histology, all received extended field radiotherapy. Only 2 were identified on pre-operative CT/MRI imaging. 3 of 10 suspected node-positive cases on CT/MRI had negative histology. Para-aortic lymphadenectomy led to alteration in staging and radiotherapy management in 8 (8%, CI: 3.7%, 14.6%) patients. Mean overall survival 42.81 months (SD = 31.79 months). Survival was significantly higher for women undergoing PAN (50.57 (SD 30.7) months) compared to those who didn't (31.27 (SD 32.5) months)Conclusion Laparoscopic retroperitoneal para-aortic lymphadenectomy is an acceptable procedure which can guide treatment in women with locally advanced cervical cancer.